2016
DOI: 10.1128/jcm.00548-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multiple Methods for Detection of Gastrointestinal Colonization of Carbapenem-Resistant Organisms from Rectal Swabs

Abstract: bRectal swabs from high-risk patients were screened for carbapenem-resistant organisms (CROs) using several methods. The direct MacConkey plate method was the most sensitive for CROs (95%), while chromID CARBA and the Check-Direct CPE screen assay were the most sensitive for the detection of carbapenemase-producing organisms (CPOs) (100%; all bla KPC ). All methods had a specificity of >90% for CROs, and for CPOs, the specificity ranged from 85 to 98%. Broth enrichment methods performed poorly compared to dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…MC-ECC showed better recoveries than chromID CARBA and CHROMagar KPC, although six IMP-positive strains were not recovered. This result is similar to previous reports [7, 16, 17]. IMP-producing CPE was also difficult to detect when a small number was inoculated.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…MC-ECC showed better recoveries than chromID CARBA and CHROMagar KPC, although six IMP-positive strains were not recovered. This result is similar to previous reports [7, 16, 17]. IMP-producing CPE was also difficult to detect when a small number was inoculated.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, among several types of carbapenemases, enzymes such as OXA-48 and IMP have low capability of hydrolysing carbapenems [6]. These data indicate the difficulties in screening for CPE in stool specimens [35, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…3 Colonies growing within 27 mm of ertapenem and 32 mm of meropenem were identified by matrix-assisted laser-desorption ionization time-of-flight mass spectrometry (Bruker Daltonics), and carbapenem antimicrobial susceptibility testing (ertapenem, meropenem and imipenem) was performed by disk diffusion applying Clinical and Laboratory Standards Institute guidelines. 4 Enterobacteriaceae resistant to ertapenem, meropenem, and/or imipenem were categorized as CRE.…”
Section: Methodsmentioning
confidence: 99%
“…Some data suggest that directly inoculating chromogenic agar from rectal swabs may compromise the sensitivity for detecting CRE (48). However, other studies have found that broth enrichment is not required and that direct inoculation of rectal swabs on chromogenic medium is comparable or superior to that in the CDC broth enrichment method (15,81).…”
Section: Growth-based Phenotypic Assays For Cr-nfmentioning
confidence: 95%
“…Another significant disadvantage is the long turnaround time of up to 4 days. Additionally, although the broth enrichment was designed to increase sensitivity, it may in fact hinder the recovery of CROs with low carbapenem MICs or low inocula in the presence of high inocula of competing organisms (15,81). A second method using standard laboratory medium involves direct inoculation of a MacConkey agar plate and the placement of carbapenem disks between the juncture of quadrants 1 and 2 and juncture of quadrants 2 and 3.…”
Section: Growth-based Phenotypic Assays For Cr-nfmentioning
confidence: 99%